Education for nation-building - Abdul Razak, Dzulkifli (Sun Media Corporation Sdn Bhd, 2019)
I OFTEN wonder why we still need to have the lyrics of Negaraku projected each time on the screen during official events. After more than 60 years of Merdeka I reckon that all Malaysians attending such official events are able to sing the national anthem by heart. I recall how it was for me at a tender age in school, where the classes were more heterogeneous than today.